Ion acoustic waves in lunar wake plasma - Sreeraj, T.; Singh, S. V.; Lakhina, G. S. (My University, 2023)
Kinetic theory of low frequency electrostatic waves is carried out in the lunar wake plasma modelled by kappa electrons, kappa-beam electrons, Maxwell–Boltzmann distributed protons and doubly charged Helium ions. The present work is motivated by observation of electrostatic waves on the outbound side of the first lunar wake flyby of the mission Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon’s Interaction with the Sun (ARTEMIS) probe P1. The dispersion characteristics of electrostatic waves which are identified as ion-acoustic waves are carried out for the observational plasma parameters. The frequencies of the ion acoustic waves derived from the model corresponding to peak growth rates are f 6 0:02f pe; (f pe being electron plasma frequency) which matches with the frequency of the waves observed by wave burst 1 (WB1) in the lunar wake (Tao et al., 2012). Our theoretical analysis reveals that in order to excite the low-frequency wave modes, low-energy electron beams are required which are not apparent in the observations. Ó 2023 COSPAR. Published by Elsevier B.V. All rights reserved.
Keywords: Electrostatic wave; Kinetic theory; Lunar wake; Solar wind